Log Periodic Dipole Array Antenna for Tv White Space Application - Muhkus, Teguh Imamul Azmi; Homam, Mariyam Jamilah; Ramli, Mohd Efandi (Evolution in Electrical and Electronic Engineering, 2022)
In this project, a Log Periodic Dipole Array (LPDA) antenna is designed to operate within the TV White Space (TVWS) spectrum ranging between 400 MHz to 800 MHz in the UHF band. The aim in designing the LPDA is to achieve Voltage Standing Wave Ratio (VSWR) < 1.5, Gain > 10 dBi, and Front-to-Back (F/B) Ratio > 20 dB. Each component of the proposed LPDA’s structure is calculated using classic Carrel mathematical calculation for LPDA designing, which are then simulated using CST Studio Suite software. The simulation result shows the LPDA achieved value of 13.5 dB.